2015
DOI: 10.5455/ijmsph.2015.0110201432
|View full text |Cite
|
Sign up to set email alerts
|

Health problems in children and associated remedial measures in Punjab, India

Abstract: Background: Majority of child deaths that occur worldwide are due to preventable causes. Maternal practices regarding children's health care have been recognized as an important factor behind mortality. Improving families' care-seeking behavior can significantly reduce child morbidity and mortality in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The most common morbidity affecting the children in the present study was Acute respiratory infections similar to the findings of many other studies. 3,4,[6][7][8]12,13 On the contrary few studies 1,2,11,14 have found diarrhea as the most common morbidity and a couple of others 9,15 have found anemia.…”
Section: Discussionmentioning
confidence: 99%
“…The most common morbidity affecting the children in the present study was Acute respiratory infections similar to the findings of many other studies. 3,4,[6][7][8]12,13 On the contrary few studies 1,2,11,14 have found diarrhea as the most common morbidity and a couple of others 9,15 have found anemia.…”
Section: Discussionmentioning
confidence: 99%